Desain dan Implementasi Sistem Layanan Umum Reservasi Bus pada Balai Kota Makassar Menggunakan Metode Model View Control (MVC) - Reza Maulana; Muniardi Muniardi (Jurusan Sistem Informasi Universitas Islam Negeri Alauddin Makassar, 2021)
The Makassar City Tourism Office is an element of implementing government affairs in the tourism sector which is the regional authority. One of the tasks carried out is to provide transportation to access tourist attractions in Makassar City, especially in South Sulawesi Province. There are several obstacles, one of which is when a borrower makes a vehicle loan application, it takes days until it is approved by the Head of the Makassar City Tourism Office. In addition, the borrower cannot track the application letter submitted. This is what makes researchers want to create a system for designing and implementing a public service system for bus loan reservations at the Makassar City Tourism Office based on a website. This research uses qualitative research, while data collection used is observation and interviews. This system includes several contents, namely vehicle lending, monitoring letters, approvals, users and invoices. Design and Implementation of Bus Loan Reservation Public Service Systems at the Makassar City-based Tourism Office This website was created using the PHP programming language, Codeigniter Framework and MySQL as its database. This system uses the Blackbox testing method. The conclusion of this research is that it can make it easier to borrow vehicles, monitor letters and vehicle management.